Biology and Transmission Dynamics of Aedes flavivirus. Issue 2 (22nd January 2022) - Peinado, Stephen A; Aliota, Matthew T; Blitvich, Bradley J; Bartholomay, Lyric C
Abstract: Aedes albopictus (Skuse) and Aedes aegypti (Linnaeus) (Diptera: Culicidae) mosquitoes transmit pathogenic arthropod-borne viruses, including dengue, chikungunya, and Zika viruses, with significant global health consequences. Both Ae. albopictus and Ae. aegypti also are susceptible to Aedes flavivirus (AEFV), an insect-specific flavivirus (ISF) first isolated in Japan from Ae. albopictus and Ae. flavopictus . ISFs infect only insect hosts and evidence suggests that they are maintained by vertical transmission. In some cases, ISFs interfere with pathogenic flavivirus infection, and may have potential use in disease control. We explored the host range of AEFV in 4 genera of mosquitoes after intrathoracic injection and observed greater than 95% prevalence in the species of Aedes and Toxorhynchites tested. Anopheles and Culex species were less permissive to infection. Vertical transmission studies revealed 100% transovarial transmission and a filial infection rate of 100% for AEFV in a persistently-infected colony of Ae. albopictus . Horizontal transmission potential was assessed for adult and larval mosquitoes following per os exposures and in venereal transmission experiments. No mosquitoes tested positive for AEFV infection after blood feeding, and infection with AEFV after sucrose feeding was rare. Similarly, 2% of adult mosquitoes tested positive for AEFV after feeding on infected cells in culture as larvae. Venereal transmission of AEFV was most frequently observed from infected males to uninfected females as compared with transmission from infected females to uninfected males. These results reveal new information on the infection potential of AEFV in mosquitoes and expand our understanding of both vertical and horizontal transmission of ISFs.